SYNTHESIS OF BROMINATED QUINOLINES - Okten, Salih; Eyigun, Dilek; Cakmak, Osman (YILDIZ TECHNICAL UNIV, 2015)
this study, bromination reactions of 1,2,3,4-tetrahydroquinoline by molecular bromine and aromatization reactions of brominated tetrahydroquinolines were reinvestigated. Optimal reaction conditions were established for 6-Bromo-1,2,3,4-tetrahydroquinoline (6-BrTHQ) and 6,8-dibromo-1,2,3,4-tetrahydroquinoline (6,8-diBrTHQ). Improved yields and more shortened reaction times were described for the conversion of 6-BrTHQ and 6,8-diBrTHQ into 6-bromoquinoline and 6,8-dibromoquinoline.
Keywords: Quinoline; tetrahydroquinoline; bromoquinoline; bromination; aromatization; DDQ; DERIVATIVES; AGENTS; Engineering